A study and design of CMOS H-Tree clock distribution network in system-on-chip - Loo, Wei-Khee; Tan, Kok-Siang; Teh, Ying-Khai (2009)
A design of a low skew clock distribution network is presented based on the TSMC 0.18 mu m CMOS technology. This work first investigated various aspects in designing a clock distribution network. After that, the design methodology for the chosen H-Tree clock network topology is presented. A series of design performance analyses such as clock delay, skew, rise and fall time, supply voltage and temperature variations and power consumption were compared for both pre-layout and post-layout simulation results. Pre-layout and post-layout simulation results validated the 3-segment pi-model. The clock network designed is able to operate up to maximum clock speed of 1.1GHz for a 1 x 1 mm(2) chip with zero skew.